If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 24 + -8k = -7k Solving 24 + -8k = -7k Solving for variable 'k'. Move all terms containing k to the left, all other terms to the right. Add '7k' to each side of the equation. 24 + -8k + 7k = -7k + 7k Combine like terms: -8k + 7k = -1k 24 + -1k = -7k + 7k Combine like terms: -7k + 7k = 0 24 + -1k = 0 Add '-24' to each side of the equation. 24 + -24 + -1k = 0 + -24 Combine like terms: 24 + -24 = 0 0 + -1k = 0 + -24 -1k = 0 + -24 Combine like terms: 0 + -24 = -24 -1k = -24 Divide each side by '-1'. k = 24 Simplifying k = 24
| 4.9(4+3x)-7.6=12 | | 2x-8+2=1 | | (x+11)2-11=0 | | -z+1=z-1 | | 0.13x-0.52=1.48x-3.523 | | X^6+8=0 | | (x+9)2-100=0 | | 3x-70=x | | 7x+5(1x+-1)=5+12x | | 7p-3=p+6 | | -5(t-2)+9t=6t-2 | | 4x+5y+7x+3y= | | (x-5)2-16=0 | | 3(4x-8)+1=12x-23 | | k+5=3-w | | 3x=-5y+4 | | -3+2=-10+3x | | 3.6+x=4.9 | | 8.21m=49.26 | | 4x+7=4(x+3) | | (x-2)2=144 | | -6(-7x-5)-2x=-1 | | 61+2x= | | 45+4x= | | -(1+7)-(-7-x)=36 | | -3(7+g)=9 | | 9114=93k | | 5(x-7)-3=-38 | | 3n+(12-5n)=22 | | 2/5-9=4 | | 4x^2-17x+25=3x+4 | | x=18.2-.4y |